Some Qualitative and Rheological Properties of Virgin Olive Oil- Apple Vinegar Salad Dressing Stabilized With Xanthan Gum - Solmaz Abedinzadeh; Mohammadali Torbati; Sodeif Azadmard-Damirchi (Tabriz University of Medical Sciences, 2016)
Purpose: Lipid oxidation and rheological properties are the main qualitative parameters determined in food emulsions. Salad dressings are food emulsions important in our daily diet, but conventional salad dressings have high amounts of cholesterol and saturated fatty acids because of egg yolk in their formulations. There are many studies on the modification of salad dressing formulations to replace egg yolk and saturated fats. The present study describes new formulation of salad dressing with olive oil and apple vinegar to produce a functional food product. Methods: This study investigated the qualitative properties, oxidative stability, rheological behavior and microstructure of the salad dressing without egg yolk. Oil-in-water emulsions were prepared with virgin olive oil and apple vinegar stabilized with various percentages of xanthan (T1: 0.25%, T2: 0.5%. T3: 0.75%). Samples were stored at refrigerator for 90 days and experiments were performed at production day and during storage. Results: The obtained results showed that peroxide value was increased for all samples during storage, but it was at an acceptable level. Fatty acid changes were not significant during storage. Droplet size was reduced by increasing xanthan gum. T2 had the best rheological properties during storage. Generally, T2 and T3 had higher scores and were more acceptable in organoleptic assay. Conclusion: Obtained results showed that T2 had suitable qualitative and rheological properties and can be a proper egg yolk free salad dressing to introduce to the market.